Diagnosis and management of pulmonary toxicity associated with cancer immunotherapy - Rashdan, Sawsan (Lancet Respir Med, 2018)
Pulmonary toxicity of cancer immunotherapies has emerged as an important clinical event that requires prompt identification and management. Although often referred to as pneumonitis, pulmonary toxicity associated with immunotherapy covers a broad and overlapping spectrum of pulmonary manifestations, and, once suspected, the range of differential diagnoses of infectious and neoplastic processes might make the diagnostic process challenging for physicians. Optimal care can require multidisciplinary effort by pulmonologists, medical oncologists, and radiologists, and awareness of the possibility of treatment-induced pulmonary toxicity by emergency department and primary care physicians. This Viewpoint gives an overview of the diagnosis and management of pulmonary toxicity arising from cancer immunotherapy, including widely used treatments, such as immune checkpoint inhibitors, and emerging therapies, such as chimeric antigen receptor T cells.